Putin After 2024 : More Power or More Predictability? - Cheang, Chris (2020)
Putin’s recent constitutional proposals have laid the basis for a post-Putin era of stability, and above all, predictability in the political system. They also pointed to his probable successor after his current term ends in 2024, while he plays a likely elder statesman role.